8p23.1 duplication detected by array‐CGH with complete atrioventricular septal defect and unilateral hand preaxial hexadactyly1. Issue 3 (12th February 2013) - Zhang, Yanliang; Li, Ya; Wang, Yuming; Shan, Bin; Duan, Yong
Abstract 8p23.1 duplication syndrome is a genomic condition with variable phenotype. Isolated 8p23.1 duplication is rare. Here, we report on additional isolated 8p23.1 duplication in a fetus with complete atrioventricular septal defect and right hand preaxial hexadactyly diagnosed by array comparative genomic hybridization (array‐CGH). Array‐CGH indicated an ∼1.43 Mb duplication between 8p23.1 olfactory receptor/defensin repeats (ORDRs) in this case, which contains 27 genes of which 21 are known and 6 are novel, including GATA4 and SOX7 and one micro‐RNA gene. In order to better understanding the genotype–phenotype association of 8p23.1 duplications, we summarized the present case and 10 previously reported patients with isolated 8p23.1 duplications between ORDRs and found that minor anomalies (6/11), congenital heart defect (6/11), developmental delay (5/11), and neurodevelopmental problems (5/11) are recurrent manifestations in 8p23.1 duplication patients. Thus, we suggest that 8p23.1 duplications between ORDRs generally result in clinical phenotypes and the phenotypes vary between patients. Because true duplications and euchromatic variants (EVs) of 8p23.1 are cytogenetically indistinguishable and usually lead to different clinical results, it is necessary to differentiate 8p23.1 duplications from EVs using molecular cytogenetic techniques. © 2013 Wiley Periodicals, Inc.